Aplikasi Rekomendasi Menu Makanan Harian Menggunakan Algoritma Metode KNN - Nafi, Tri Maula; Mujiyono, Sri (Institut Teknologi Garut, 2025)
This food menu recommendation app utilizes the K-Nearest Neighbors (KNN) algorithm to provide menu suggestions that suit the nutritional needs and preferences of users. The system analyzes various factors, including calories, protein, fat, and carbohydrates, in order to generate accurate and relevant recommendations. Users can enter information related to their nutritional needs and food preferences, such as their favorite types of food and allergies, to get the right menu suggestions. Through this application, users are expected to receive healthy menu recommendations that suit their individual needs, which in turn can increase awareness of the importance of a nutritious diet and overall health. With a data-driven approach, this app is an effective solution for those who want to make healthier food choices and support the achievement of their desired health and nutritional goals. In addition, this app can also contribute to building better eating habits among the community.